Competitive Inhibition by Lithium and Hydrogen lons of the Effect of Calcium on the Aggregation of Rabbit Platelets - Anderson, Esther R.; Foulks, J. G (Thrombosis and Haemostasis, 1976)
ADP-induced platelet aggregation and shape change were monitored optically in citrated rabbit platelet-rich plasma (PRP) diluted with isotonic salt solutions. Lithium (Li) produced a concentration-dependent reduction in the rate of platelet aggregation but had no discernible effect on the shape change which precedes aggregation. When PRP was pre-incubated with Li, the inhibitory effect of the ion was independent of the duration and temperature of the treatment. The inhibitory effect of Li also was observed in heparinized PRP or when 5-HT was used as the aggregation-inducing agent. When Li was combined with aggregation inhibitors which enhance platelet cyclic AMP content either by activating adenylate cyclase or by inhibiting phosphodiesterase, only additive effects were observed. The inhibitory effect of Li was opposed by added calcium. Kinetic evaluation of the interaction between Li and Ca indicated that their antagonism was competitive. Added calcium also displayed competitive antagonism toward the aggregation inhibiting effect of increased hydrogen ion concentration in the pH range between 6 and 8.